1991
DOI: 10.1136/gut.32.9.1071
|View full text |Cite
|
Sign up to set email alerts
|

Double blind, placebo controlled trial of metronidazole in Crohn's disease.

Abstract: A double blind study compared the efficacy of metronidazole in two doses (20 mg/kg, 10 mg/ kg) with placebo in patients with Crohn's disease. One hundred and five patients participated but only 56 completed the 16 week study -21 were withdrawn for deterioration of symptoms, 17 for adverse experiences, and 11 for protocol violation. Significant improvement in disease activity as measured by the Crohn's disease activity index (metronidazole 20 mg/ kg, 97 units; metronidazole 10 mg/kg, 67 units; placebo -1 unit, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
256
0
6

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 481 publications
(267 citation statements)
references
References 13 publications
5
256
0
6
Order By: Relevance
“…This fact is supported by the therapeutic benefits of antibiotic and probiotic treatment in IBD patients, 40,41 the observation that specific enteric flora are found more commonly in patients than in controls, 42,43 and studies in a variety of murine strains in which 'spontaneous' colitis seems to be entirely dependent on the presence of a luminal flora. [44][45][46] Autophagy has an important role in physiological and pathological processes, such as degradation of cytoplasmic components, cellular response to nutrient starvation and apoptosis.…”
Section: Discussionmentioning
confidence: 94%
“…This fact is supported by the therapeutic benefits of antibiotic and probiotic treatment in IBD patients, 40,41 the observation that specific enteric flora are found more commonly in patients than in controls, 42,43 and studies in a variety of murine strains in which 'spontaneous' colitis seems to be entirely dependent on the presence of a luminal flora. [44][45][46] Autophagy has an important role in physiological and pathological processes, such as degradation of cytoplasmic components, cellular response to nutrient starvation and apoptosis.…”
Section: Discussionmentioning
confidence: 94%
“…Notably, reductions in the titer of antibody to F. varium appeared to correlate to these improvements. Several groups have demonstrated the benefi t of antibiotics in Crohn ' s colitis and ileocolitis, but not isolated small bowel disease, especially for metronidazole ( 64 ). A recent 402 patient prospective randomized trial reported signifi cant induction of remission of moderately active Crohn ' s disease over 12 weeks by 800 mg b.i.d.…”
Section: Therapeutic Approachesmentioning
confidence: 99%
“…Metronidazole, 10 or 20 mg / kg, has been compared with placebo for mild to moderate disease and was not more e ective than placebo for inducing remission (100) . A post hoc subgroup analysis indicated that metronidazole might be e ective in patients with colonic involvement (ileocolitis and colitis) (100) .…”
Section: Mild To Moderate Active Diseasementioning
confidence: 99%